The risk-taking channel of monetary policy transmission in the euro area - Matthias Neuenkirch; Matthias Nöckel (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2017)
In this paper, we provide evidence for a risk-taking channel of monetary policy transmission in the euro area. Our dataset covers the period 2003Q1-2016Q2 and includes, in addition to the standard variables for real GDP growth, inflation, and the main refinancing rate, indicators of bank lending standards and bank lending margins. Based on vector autoregressive models with (i) recursive identification and (ii) sign restrictions, we show that banks react quickly and aggressively to an expansionary monetary policy shock by decreasing their lending standards. The banks' efforts to keep their lending margins stable are successful, as we find only an insignificant decrease in the margins over the medium-run.
Keywords: E44; E51; E52; E58; G28; 330; European Central Bank; Macroprudential Policy; Monetary Policy Transmission; Risk-Taking Channel; Vector Autoregression